2021
DOI: 10.3389/fcell.2021.649265
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Anlotinib in Pancreatic Cancer and Development of an Anlotinib-Related Prognostic Signature

Abstract: Aberrant regulation of angiogenesis involves in the growth and metastasis of tumors, but angiogenesis inhibitors fail to improve overall survival of pancreatic cancer patients in previous phase III clinical trials. A comprehensive knowledge of the mechanism of angiogenesis inhibitors against pancreatic cancer is helpful for clinical purpose and for the selection of patients who might benefit from the inhibitors. In this work, multi-omics analyses (transcriptomics, proteomics, and phosphoproteomics profiling) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Since its introduction as a broad-spectrum anti-tumor-targeted drug, anlotinib has made significant progress in the treatment of cancers and has played a role in a wide range of malignancies (34)(35)(36)(37). Zhang et al discovered that anlotinib inhibited PC cell proliferation while inducing apoptosis (38). Yang et al demonstrated that anlotinib killed PC cells both in vitro and in vivo (39).…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction as a broad-spectrum anti-tumor-targeted drug, anlotinib has made significant progress in the treatment of cancers and has played a role in a wide range of malignancies (34)(35)(36)(37). Zhang et al discovered that anlotinib inhibited PC cell proliferation while inducing apoptosis (38). Yang et al demonstrated that anlotinib killed PC cells both in vitro and in vivo (39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have achieved effective results not only in NSCLC and SCLC (10), but also in liver cancer (19,41) or refractory metastatic colorectal cancer (42). There are currently more (15) revealed that anlotinib had a profound inhibitory effect on ribosomes, and regulated the cell cycle, RNA metabolism, and lysosomes as determined by transcriptomics, proteomics, and phosphor proteomics profiling. These studies suggested that anlotinib plus chemotherapy was a feasible regimen for the treatment of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC tissues have high expression of VEGF, which is associated with liver metastasis in PDAC and is predictive of poor prognosis (14). Anlotinib exerted noteworthy cytotoxicity on PDAC cells (15). Anlotinib can inhibit proliferation, induce G2/M phase arrest, and trigger apoptosis in PDAC and hepatocellular carcinoma (HCC) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anlotinib may play a therapeutic role in a variety of malignancies. Zhang et al revealed that anlotinib inhibited pancreatic cancer cell proliferation and induced its apoptosis (21). Yang et al found that anlotinib had a killing effect on pancreatic cancer cells both in vivo and in vitro (22).…”
Section: Discussionmentioning
confidence: 99%